2019
DOI: 10.3390/molecules25010061
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Echinulin-Related Indolediketopiperazines from the Marine Sediment-Derived Fungus Aspergillus niveoglaucus

Abstract: Seven known echinulin-related indolediketopiperazine alkaloids (1–7) were isolated from the Vietnamese sediment-derived fungus Aspergillus niveoglaucus. Using chiral HPLC, the enantiomers of cryptoechinuline B (1) were isolated as individual compounds for the first time. (+)-Cryptoechinuline B (1a) exhibited neuroprotective activity in 6-OHDA-, paraquat-, and rotenone-induced in vitro models of Parkinson’s disease. (−)-Cryptoechinuline B (1b) and neoechinulin C (5) protected the neuronal cells against paraquat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 44 publications
1
15
0
1
Order By: Relevance
“…(−)-Cryptoechinuline B ( 212 ) and neoechinulin C ( 215 ) protected the Neuro-2a cells against paraquat toxicity. Neoechinulin B ( 214 ) exhibited cytoprotective activity against rotenone toxicity, and neoechinulin ( 213 ) showed activity against 6-OHDA [ 111 , 112 ].…”
Section: Radical Scavenging and Antioxidant Activitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…(−)-Cryptoechinuline B ( 212 ) and neoechinulin C ( 215 ) protected the Neuro-2a cells against paraquat toxicity. Neoechinulin B ( 214 ) exhibited cytoprotective activity against rotenone toxicity, and neoechinulin ( 213 ) showed activity against 6-OHDA [ 111 , 112 ].…”
Section: Radical Scavenging and Antioxidant Activitiesmentioning
confidence: 99%
“…SCSIO z015 Okinawa Trough, The East China Sea DPPH radical scavenging [ 107 ] Eurotiumins A–C ( 196 – 198 ) Eurotium sp. SCSIO F452 The South China Sea DPPH-radical scavenging [ 108 ] Eurotinoids A–C ( 199 – 204 ) [ 109 ] (+)-Dihydrocryptoechinulin D ( 205 ) Cytotoxicity (SF-268, HepG2) DPPH-radical scavenging (-)-Dihydrocryptoechinulin D ( 206 ) (+)-Euroticin B ( 207 ) Antioxidant activities [ 110 ] (–)-Euroticin B ( 208 ) Niveoglaucin A ( 209 ) Aspergillus niveoglaucus Nha Trang Bay, The South China Sea Suppression of ROS hyperproduction, Neuroprotective activity [ 111 ] Flavoglaucin ( 210 ) …”
Section: Table A1mentioning
confidence: 99%
See 1 more Smart Citation
“…Многие из них показали in vitro хорошую активность на различных моделях болезни Паркинсона. Было выделено два энантиомера криптоэхинулина В. Один из изомеров, (+)-криптоэхинулин B, демонстрировал хороший нейропротекторный эффект во всех экспериментах, а для его антипода такой эффект наблюдался только при использовании некоторых стимуляторов признаков этой болезни [9].…”
Section: новые биопрепараты для медициныunclassified
“…Diketopiperazine alkaloids have shown various biological activities, including cytotoxic [ 10 , 11 , 12 , 13 ], antiphytopathogenic [ 14 ], anticancer [ 15 ] and neuroprotective effects [ 16 ]. Earlier it was reported that cryptoechinulin B and other echinuline-related compounds increased the viability of paraquat (PQ)-treated Neuro-2a cells, suppressing the upregulation of intracellular reactive oxygen species [ 17 ]. PQ is a bipyridyl quaternary ammonium herbicide and PQ poisoning is one of the leading intoxications worldwide.…”
Section: Introductionmentioning
confidence: 99%